Legal provisions regulating intellectual property rights (patent as a model) - Zeyad Tareq Ibrahim (Genius Journals, 2022)
The patent is of great importance because of the benefits it provides that encourage creators in various fields by recognizing their works or giving them fair monetary and moral rewards. the countries of the world have realized the seriousness of patent infringement crimes and the necessity of punishing their perpetrators. They worked on the development of many legal legislations at the international and internal levels with the aim of protecting intellectual property rights, foremost of which is the patent, and working to bridge legal gaps and prevent abuse, with the approval of a group of Protection measures at its various stages.
Keywords: Legal; property rights; prevent; abuse